NEW EMPLOYEE SELECTION METHOD WEIGHTED PRODUCT AT PT. XYZ - Fried Sinlae (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Weighted Product (WP) Methodology Implementation System for Employee Recruitment at PT. Web-Based XYZ conducted research on decision support systems with a website platform for PT. XYZ. The data collection method was carried out for research using the literature study method from existing theories, interviews, several discussions as well as questions and observations at research sites. Using the Weighted Product (WP) Methodology aims to provide a solution to the problems that exist at PT. XYZ, for the basis of a computational assessment. PT assistant system. XYZ to conduct elections in determining employees who are selected from the best of all existing candidates. As well as the selection presented in the system. Research shows that this website system can make it easier for PT. XYZ to make selections in choosing prospective employees with specifications with the help of the Weighted Product (WP) methodology. So it can be said that the values and results that can be displayed still provide eligibility and suitability of the system that can be applied the same as the manual system that runs for the selection of new PT employees. XYZ.            Keywords: Methodology Weighted Product; SPK; Website; Warehouse  Abstrak: Sistem Penerapan Metodologi Weighted Product (WP) Untuk Penerimaan Karyawan di PT. XYZ Berbasis Web melakukan riset tentang sistem pendukung keputusan dengan platform website untuk PT. XYZ. Metode pengambilan data-data dikerjakan untuk riset me-manfaatkan metode studi pustaka dari teori-teori yang ada, wawancara beberapa diskusi serta pertanyaan dan observasi ke tempat riset. Menggunakan Metodologi Weighted Product (WP) bertujuan agar memberikan solusi dari masalah yang ada pada pada PT. XYZ, untuk dasar penilaian secara perhitungan. Sistem pembantu PT. XYZ agar melakukan pemilihan dalam menentukan karyawan yang terpilih dari yang terbaik dari semua kandi-dat yang ada. Serta penseleksian disajikan dalam sistem. Pada riset menampilkan kalua sistem website ini bisa memudahkan PT. XYZ untuk melakukan pemilihan dalam memilih calon karyawan dengan spesifikasi oleh bantuan metodologi Weighted Product (WP). Jadi bisa dikatakan kalau nilai dan hasil dapat ditampilkan masih memberikan kelayakan serta kecocokan sistem dapat diterapkan sama seperti manual sistem yang berjalan untuk seleksi karyawan baru PT. XYZ. Kata kunci: Metodologi Weighted Product; SPK; Website; Warehouse